Investigation of a simple energy management system of a hybrid PV-battery system - Mahdi, Baqer Saleh; Sulaiman, Nasri; Shehab, Mohanad Abd; Hassan, Siti Lailatul Mohd; Shafie, Suhaidi; Hizam, Hashim (Association of Polish Electrical Engineers, 2024)
Growing energy demands are expected to render existing energy resources insufficient. Solar energy faces challenges in terms of providing continuous and reliable power supply to consumers. However, it has become increasingly important to implement renewable energy (RE) and energy management (EM) systems to increase the supply of power, improve efficiency, and maintain the stability of energy systems. As such, this present study integrated energy storage (ES) devices; namely, batteries and direct current (DC) to DC converters; into energy systems that support battery operation and effectively manage power flow, especially during peak load demands. The proposed system also addresses low solar irradiation and sudden load change scenarios by enabling the battery to operate in a discharge state to supply power to the load. Conversely, when the demand matches or exceeds the available solar energy, the battery is charged using solar power. The proposed system highlights the significance of RE systems and EM strategies in meeting growing energy demands and ensuring a reliable supply of power during solar variability and fluctuating loads. A MATLAB® Simulink model was used to evaluate the integration of a 200 kW photovoltaic (PV) array with a 380 V grid and 150 kW battery. The loads, consisting of a 100 kW and a 150 kW unit, were parallel connected. The results indicated that boost and three-phase (3Ph) inverters can be used to successfully integrate PV systems to the power grid to supply alternating current (AC) power. The inclusion of a battery also addressed power shortages during periods of insufficient power generation and to store surplus power.